2012
DOI: 10.1371/journal.pone.0032532
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Brain Networks in Board Game Experts: Insights from a Domain-Related Task and Task-Free Resting State

Abstract: Cognitive performance relies on the coordination of large-scale networks of brain regions that are not only temporally correlated during different tasks, but also networks that show highly correlated spontaneous activity during a task-free state. Both task-related and task-free network activity has been associated with individual differences in cognitive performance. Therefore, we aimed to examine the influence of cognitive expertise on four networks associated with cognitive task performance: the default mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 71 publications
(128 reference statements)
10
53
0
3
Order By: Relevance
“…The changes in the caudate nucleus may be due to increased efficiency in juggling the lexico-semantic sets of two languages required for the execution of simultaneous interpretation. Our findings add weight to the notion that the right striatum occupies a key position in evolving expert performance, as has previously been shown in professional musicians (James et al, 2013), chess players (Haslinger et al, 2004), athletes (Duan et al, 2012) and here, in simultaneous interpreters. This notion is compatible with the wideranging roles of the basal ganglia, which include cognitive pattern generation (Milton et al, 2007;Yarrow et al, 2009), action pattern selection and refinement (Graybiel, 1997), and prediction (Houk et al, 2007), and in learning, memory and motivation more generally.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The changes in the caudate nucleus may be due to increased efficiency in juggling the lexico-semantic sets of two languages required for the execution of simultaneous interpretation. Our findings add weight to the notion that the right striatum occupies a key position in evolving expert performance, as has previously been shown in professional musicians (James et al, 2013), chess players (Haslinger et al, 2004), athletes (Duan et al, 2012) and here, in simultaneous interpreters. This notion is compatible with the wideranging roles of the basal ganglia, which include cognitive pattern generation (Milton et al, 2007;Yarrow et al, 2009), action pattern selection and refinement (Graybiel, 1997), and prediction (Houk et al, 2007), and in learning, memory and motivation more generally.…”
Section: Discussionsupporting
confidence: 88%
“…Expert musicians carrying out a bimanual coordination task display less right striatal activation than do non-musicians (Haslinger et al, 2004). Duan et al (2012) showed that chess masters had increased resting-state functional connectivity between the caudate nuclei and the default mode network. While music and strategic planning are often thought of as principally cognitive tasks, functional plasticity also occurs in the basal ganglia of experts in an apparently unrelated domain: golf.…”
Section: The Role Of the Caudate Nucleus In Expertisementioning
confidence: 99%
“…b r a i n r e s e a r c h 1 6 0 2 ( 2 0 1 5 ) 8 5 -9 5 different activities (e.g., Chinese chess) have been linked to both directions of change in functional connectivity (Duan et al, 2012;Kelly and Garavan, 2005), just as psychopathology may be associated with either higher or lower functional connectivity (Whitfield-Gabrieli et al, 2009;Zhou et al, 2007). Furthermore, the opposing nature of the correlations (i.e., significant group interaction) found in the present study suggests the possibility that the effect of long-term excessive video game play might differentially influence the brain depending on the addiction risk of each individual, as exemplified by the existence of non-addicted professional online gamers (Han et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Both the SFGp (SMA proper) and SFGam_p (preSMA) are belonged to BA 6 and are connected with sensorimotor areas (Yu et al, 2011); however, the latter shows stronger rsFC with the prefrontal areas (Lu et al, 1994;Luppino et al, 1993;Wang et al, 2005) and brain regions of the salience network (Bonnelle et al, 2012;Duan et al, 2012;Seeley et al, 2007) compared to the former. These findings were also supported by the concept that the medial SFG (preSMA) is involved in the cognitive control network (Sundermann and Pfleiderer, 2012).…”
Section: The Correspondence Between Sfg Subregions and Brodmann Areasmentioning
confidence: 99%